2019
DOI: 10.1073/pnas.1816973116
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of nitric oxide regulation of gut function

Abstract: Although morphologies are diverse, the common pattern in bilaterians is for passage of food in the gut to be controlled by nerves and endodermally derived neuron-like cells. In vertebrates, nitric oxide (NO) derived from enteric nerves controls relaxation of the pyloric sphincter. Here, we show that in the larvae of sea urchins, there are endoderm-derived neuronal nitric oxide synthase (nNOS)-positive cells expressing pan-neural marker, Synaptotagmin-B (SynB), in sphincters and that NO regulates the relaxation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 57 publications
0
15
0
3
Order By: Relevance
“…In addition, when the 5HT 2 receptor was knocked down (Fig. 3 c), the pylori of the morphants responded to neither photoirradiation nor serotonin but did respond to the nitric oxide (NO) donor S-nitroso-N-acetyl-D,L-penicillamine (SNAP) [ 23 ] (Fig. 3 d, Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, when the 5HT 2 receptor was knocked down (Fig. 3 c), the pylori of the morphants responded to neither photoirradiation nor serotonin but did respond to the nitric oxide (NO) donor S-nitroso-N-acetyl-D,L-penicillamine (SNAP) [ 23 ] (Fig. 3 d, Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S7d). This SNAP experiment was performed because we had recently reported that NO is involved in the pyloric opening in sea urchin larvae, similar to mammals [ 23 ]. The average pyloric opening rates were 4% (control with no treatment), 21.9% (control with photoirradiation), 81.6% (control with serotonin), 93.5% (control with SNAP), 0% (5HT 2 morphants with no treatment), 2.1% (5HT 2 morphants with photoirradiation), 7.5% (5HT 2 morphants with serotonin), and 84.7% (5HT 2 morphants with SNAP).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 7 ] Analysis of the relevant literature shows that NO also participates in the regulation of various physiological processes, including vascular relaxation, immune regulation, neurotransmission, bone metabolism, among many others. [ 8–13 ]…”
Section: Introductionmentioning
confidence: 99%